2020
DOI: 10.5152/ejbh.2019.4997
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Molecular Subtypes of Breast Cancer: A Single Institutional Experience of 2062 Patients

Abstract: European Journal of Breast Health (Eur J Breast Health) is an international, scientific, open access periodical published by independent, unbiased, and double-blinded peer-review principles. It is the official publication of the Turkish Federation of Breast Diseases Societies, and Senologic International Society is the official supporter of the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
34
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 27 publications
12
34
2
6
Order By: Relevance
“…This age at presentation in our current study is in agreement with a previous Togolese study were the mean age at diagnosis of cancer was 50 years [10]. This is also similar to the mean age reported in Ghanaian patients at Korle bu Hospital [16] and in Indian women [17], but different from the relatively younger age of women with breast cancer reported in several studies in others countries in Africa [12,[18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This age at presentation in our current study is in agreement with a previous Togolese study were the mean age at diagnosis of cancer was 50 years [10]. This is also similar to the mean age reported in Ghanaian patients at Korle bu Hospital [16] and in Indian women [17], but different from the relatively younger age of women with breast cancer reported in several studies in others countries in Africa [12,[18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…had positive lymph nodes and the majority had T3 or T4 tumors stage. These unfavorable clinicopathological characteristics such as high grade, large tumors size, axillary lymph node involvement and advanced stage are the same as those reported in several studies [14,15,17,21,26,27]. The advanced stage of diagnosis in our patients could be explained by the delay of consultation, the absence of national breast cancer screening program in the population, the poor health care facilities and the use of traditional medicine.…”
Section: Discussionsupporting
confidence: 85%
“…This age at presentation in our current study is in agreement with a previous Togolese study where the mean age at diagnosis of cancer was 50 years [ 10 ]. This is also similar to the mean age reported in Ghanaian patients at Korle bu Hospital [ 16 ] and in Indian women [ 17 ] but different from the relatively younger age of women with breast cancer reported in several studies in others countries in Africa [ 12 , 18 22 ].…”
Section: Discussionsupporting
confidence: 85%
“…Our study revealed that less than 10% of women with breast cancer have well-differentiated tumors, 42% had positive lymph nodes and the majority had T3 or T4 tumors stage. These unfavorable clinicopathological characteristics such as high grade, large tumors size, axillary lymph node involvement, and advanced stage are the same as those reported in several studies [ 14 , 15 , 17 , 21 , 26 , 27 ]. The advanced stage of diagnosis in our patients could be explained by the delay of consultation, the absence of a national breast cancer screening program in the population, the poor health care facilities, and the use of traditional medicine.…”
Section: Discussionsupporting
confidence: 85%
“…Our study revealed that less than 10% of women with breast cancer have well-differentiated tumors, 42% had positive lymph nodes and the majority had T3 or T4 tumors stage. These unfavorable clinicopathological characteristics such as high grade, large tumors size, axillary lymph node involvement, and advanced stage are the same as those reported in several studies [14,15,17,21,26,27]. The advanced stage of diagnosis in our patients could be explained by the delay of consultation, the absence of a national breast cancer screening program in the population, the poor health care facilities, and the use of traditional medicine.…”
Section: Discussionsupporting
confidence: 85%